Mercurial > hg > Members > kono > Proof > ZF-in-agda
changeset 105:ec6235ce0215
power set
author | Shinji KONO <kono@ie.u-ryukyu.ac.jp> |
---|---|
date | Sun, 16 Jun 2019 11:37:00 +0900 |
parents | d92411bed18c |
children | c31ac67e9ecb |
files | ordinal-definable.agda |
diffstat | 1 files changed, 70 insertions(+), 151 deletions(-) [+] |
line wrap: on
line diff
--- a/ordinal-definable.agda Sun Jun 16 02:06:09 2019 +0900 +++ b/ordinal-definable.agda Sun Jun 16 11:37:00 2019 +0900 @@ -43,7 +43,7 @@ eq-trans x=y y=z = record { eq→ = λ t → eq→ y=z ( eq→ x=y t) ; eq← = λ t → eq← x=y ( eq← y=z t) } od∅ : {n : Level} → OD {n} -od∅ {n} = record { def = λ _ → Lift n ⊥ } +od∅ {n} = record { def = λ x → x o< o∅ } postulate -- OD can be iso to a subset of Ordinal ( by means of Godel Set ) @@ -66,11 +66,11 @@ _∋_ : { n : Level } → ( a x : OD {n} ) → Set n _∋_ {n} a x = def a ( od→ord x ) -Ord : { n : Level } → ( a : Ordinal {suc n} ) → OD {suc n} +Ord : { n : Level } → ( a : Ordinal {n} ) → OD {n} Ord {n} a = record { def = λ y → y o< a } _c<_ : { n : Level } → ( x a : Ordinal {n} ) → Set n -x c< a = Ord a ∋ Ord x +_c<_ {n} x a = Ord {n} a ∋ Ord x c<→o< : { n : Level } → { x a : OD {n} } → record { def = λ y → y o< od→ord a } ∋ x → od→ord x o< od→ord a c<→o< lt = lt @@ -78,39 +78,39 @@ o<→c< : { n : Level } → { x a : OD {n} } → od→ord x o< od→ord a → record { def = λ y → y o< od→ord a } ∋ x o<→c< lt = lt -==→o≡' : {n : Level} → { x y : Ordinal {suc n} } → Ord x == Ord y → x ≡ y -==→o≡' {n} {x} {y} eq with trio< {n} x y -==→o≡' {n} {x} {y} eq | tri< a ¬b ¬c with eq← eq {x} a +==→o≡ : {n : Level} → { x y : Ordinal {suc n} } → Ord x == Ord y → x ≡ y +==→o≡ {n} {x} {y} eq with trio< {n} x y +==→o≡ {n} {x} {y} eq | tri< a ¬b ¬c with eq← eq {x} a ... | t = ⊥-elim ( o<¬≡ x x refl t ) -==→o≡' {n} {x} {y} eq | tri≈ ¬a refl ¬c = refl -==→o≡' {n} {x} {y} eq | tri> ¬a ¬b c with eq→ eq {y} c +==→o≡ {n} {x} {y} eq | tri≈ ¬a refl ¬c = refl +==→o≡ {n} {x} {y} eq | tri> ¬a ¬b c with eq→ eq {y} c ... | t = ⊥-elim ( o<¬≡ y y refl t ) -∅∨ : { n : Level } → { x y : Ordinal {suc n} } → ( Ord {n} x == Ord y ) ∨ ( ¬ ( Ord x == Ord y ) ) +∅∨ : { n : Level } → { x y : Ordinal {suc n} } → ( Ord {suc n} x == Ord y ) ∨ ( ¬ ( Ord x == Ord y ) ) ∅∨ {n} {x} {y} with trio< x y -∅∨ {n} {x} {y} | tri< a ¬b ¬c = case2 ( λ eq → ¬b ( ==→o≡' eq ) ) +∅∨ {n} {x} {y} | tri< a ¬b ¬c = case2 ( λ eq → ¬b ( ==→o≡ eq ) ) ∅∨ {n} {x} {y} | tri≈ ¬a refl ¬c = case1 ( record { eq→ = id ; eq← = id } ) -∅∨ {n} {x} {y} | tri> ¬a ¬b c = case2 ( λ eq → ¬b ( ==→o≡' eq ) ) +∅∨ {n} {x} {y} | tri> ¬a ¬b c = case2 ( λ eq → ¬b ( ==→o≡ eq ) ) -¬x∋x' : { n : Level } → { x : Ordinal {n} } → ¬ ( record { def = λ y → y o< x } ∋ record { def = λ y → y o< x } ) -¬x∋x' {n} {record { lv = Zero ; ord = ord }} (case1 ()) -¬x∋x' {n} {record { lv = Suc lx ; ord = Φ .(Suc lx) }} (case1 (s≤s x)) = ¬x∋x' {n} {record { lv = lx ; ord = Φ lx }} (case1 {!!}) -¬x∋x' {n} {record { lv = Suc lx ; ord = OSuc (Suc lx) ox }} (case1 (s≤s x)) = ¬x∋x' {n} {record { lv = Suc lx ; ord = ox}} (case1 {!!}) -¬x∋x' {n} {record { lv = lv ; ord = Φ (lv) }} (case2 ()) -¬x∋x' {n} {record { lv = lv ; ord = OSuc (lv) ox }} (case2 x) = - ¬x∋x' {n} {record { lv = lv ; ord = ox }} (case2 {!!}) +-- ¬x∋x' : { n : Level } → { x : Ordinal {n} } → ¬ ( record { def = λ y → y o< x } ∋ record { def = λ y → y o< x } ) +-- ¬x∋x' {n} {record { lv = Zero ; ord = ord }} (case1 ()) +-- ¬x∋x' {n} {record { lv = Suc lx ; ord = Φ .(Suc lx) }} (case1 (s≤s x)) = ¬x∋x' {n} {record { lv = lx ; ord = Φ lx }} (case1 {!!}) +-- ¬x∋x' {n} {record { lv = Suc lx ; ord = OSuc (Suc lx) ox }} (case1 (s≤s x)) = ¬x∋x' {n} {record { lv = Suc lx ; ord = ox}} (case1 {!!}) +-- ¬x∋x' {n} {record { lv = lv ; ord = Φ (lv) }} (case2 ()) +-- ¬x∋x' {n} {record { lv = lv ; ord = OSuc (lv) ox }} (case2 x) = +-- ¬x∋x' {n} {record { lv = lv ; ord = ox }} (case2 {!!}) -¬x∋x : { n : Level } → { x : OD {n} } → ¬ x ∋ x -¬x∋x = {!!} +-- ¬x∋x : { n : Level } → { x : OD {n} } → ¬ x ∋ x +-- ¬x∋x = {!!} oc-lemma : { n : Level } → { x : OD {n} } → { oa : Ordinal {n} } → def (record { def = λ y → y o< oa }) oa → ⊥ oc-lemma {n} {x} {oa} lt = o<¬≡ oa oa refl lt -oc-lemma1 : { n : Level } → { x : OD {n} } → { oa : Ordinal {n} } → od→ord (record { def = λ y → y o< oa }) o< oa → ⊥ -oc-lemma1 {n} {x} {oa} lt = ¬x∋x' {n} lt -- lt : def (record { def = λ y → y o< oa }) (record { def = λ y → y o< oa }) +-- oc-lemma1 : { n : Level } → { x : OD {n} } → { oa : Ordinal {n} } → od→ord (record { def = λ y → y o< oa }) o< oa → ⊥ +-- oc-lemma1 {n} {x} {oa} lt = ¬x∋x' {n} lt -- lt : def (record { def = λ y → y o< oa }) (record { def = λ y → y o< oa }) -oc-lemma2 : { n : Level } → { x a : OD {n} } → { oa : Ordinal {n} } → oa o< od→ord (record { def = λ y → y o< oa }) → ⊥ -oc-lemma2 {n} {x} {oa} lt = {!!} +-- this one cannot be proved because if we have this OD and Ordinal has one to one corespondence +-- oc-lemma2 : { n : Level } → { x a : OD {n} } → { oa : Ordinal {n} } → oa o< od→ord (record { def = λ y → y o< oa }) → ⊥ _c≤_ : {n : Level} → OD {n} → OD {n} → Set (suc n) a c≤ b = (a ≡ b) ∨ ( b ∋ a ) @@ -125,22 +125,28 @@ def-o< x<y = x<y sup-od : {n : Level } → ( OD {n} → OD {n}) → OD {n} -sup-od ψ = ord→od ( sup-o ( λ x → od→ord (ψ (ord→od x ))) ) +sup-od ψ = record { def = λ y → y o< ( sup-o ( λ x → od→ord (ψ (ord→od x ))) ) } sup-c< : {n : Level } → ( ψ : OD {n} → OD {n}) → ∀ {x : OD {n}} → def ( sup-od ψ ) (od→ord ( ψ x )) -sup-c< {n} ψ {x} = def-subst {n} {_} {_} {sup-od ψ} {od→ord ( ψ x )} - {!!} refl (cong ( λ k → od→ord (ψ k) ) oiso) +sup-c< {n} ψ {x} = def-subst {n} {_} {_} {record { def = λ y → y o< ( sup-o ( λ x → od→ord (ψ (ord→od x ))) ) }} {od→ord ( ψ x )} + lemma refl (cong ( λ k → od→ord (ψ k) ) oiso) where + lemma : od→ord (ψ (ord→od (od→ord x))) o< sup-o (λ x → od→ord (ψ (ord→od x))) + lemma = subst₂ (λ j k → j o< k ) refl diso (o<→c< (o<-subst sup-o< refl (sym diso) ) ) -od∅' : {n : Level} → OD {n} -od∅' = record { def = λ x → x o< o∅ } - -∅0 : {n : Level} → od∅ {suc n} == record { def = λ x → x o< o∅ } +∅0 : {n : Level} → record { def = λ x → Lift n ⊥ } == od∅ {n} eq→ ∅0 {w} (lift ()) eq← ∅0 {w} (case1 ()) eq← ∅0 {w} (case2 ()) ∅1 : {n : Level} → ( x : Ordinal {n} ) → ¬ ( x c< o∅ {n} ) -∅1 {n} x lt = {!!} +∅1 {n} record { lv = Zero ; ord = (Φ .0) } (case1 ()) +∅1 {n} record { lv = Zero ; ord = (Φ .0) } (case2 ()) +∅1 {n} record { lv = Zero ; ord = (OSuc .0 ox) } (case1 ()) +∅1 {n} record { lv = Zero ; ord = (OSuc .0 ox) } (case2 ()) +∅1 {n} record { lv = (Suc lx) ; ord = (Φ .(Suc lx)) } (case1 ()) +∅1 {n} record { lv = (Suc lx) ; ord = (Φ .(Suc lx)) } (case2 ()) +∅1 {n} record { lv = (Suc lx) ; ord = (OSuc .(Suc lx) ox) } (case1 ()) +∅1 {n} record { lv = (Suc lx) ; ord = (OSuc .(Suc lx) ox) } (case2 ()) ∅3 : {n : Level} → { x : Ordinal {n}} → ( ∀(y : Ordinal {n}) → ¬ (y o< x ) ) → x ≡ o∅ {n} ∅3 {n} {x} = TransFinite {n} c2 c3 x where @@ -196,89 +202,20 @@ c≤-refl : {n : Level} → ( x : OD {n} ) → x c≤ x c≤-refl x = case1 refl -o<→o> : {n : Level} → { x y : OD {n} } → (x == y) → (od→ord x ) o< ( od→ord y) → ⊥ -o<→o> {n} {x} {y} record { eq→ = xy ; eq← = yx } (case1 lt) with - yx (def-subst {n} {ord→od (od→ord y)} {od→ord x} {!!} oiso refl ) -... | oyx with o<¬≡ (od→ord x) (od→ord x) refl {!!} -... | () -o<→o> {n} {x} {y} record { eq→ = xy ; eq← = yx } (case2 lt) with - yx (def-subst {n} {ord→od (od→ord y)} {od→ord x} {!!} oiso refl ) -... | oyx with o<¬≡ (od→ord x) (od→ord x) refl {!!} -... | () - -==→o≡ : {n : Level} → { x y : Ordinal {suc n} } → ord→od x == ord→od y → x ≡ y -==→o≡ {n} {x} {y} eq with trio< {n} x y -==→o≡ {n} {x} {y} eq | tri< a ¬b ¬c = ⊥-elim ( o<→o> eq (o<-subst a (sym ord-iso) (sym ord-iso ))) -==→o≡ {n} {x} {y} eq | tri≈ ¬a b ¬c = b -==→o≡ {n} {x} {y} eq | tri> ¬a ¬b c = ⊥-elim ( o<→o> (eq-sym eq) (o<-subst c (sym ord-iso) (sym ord-iso ))) - -≡-def : {n : Level} → { x : Ordinal {suc n} } → x ≡ od→ord (record { def = λ z → z o< x } ) -≡-def {n} {x} = ==→o≡ {n} (subst (λ k → ord→od x == k ) (sym oiso) lemma ) where - lemma : ord→od x == record { def = λ z → z o< x } - eq→ lemma {w} lt = {!!} - -- ?subst₂ (λ k j → k o< j ) diso refl (subst (λ k → (od→ord ( ord→od w)) o< k ) diso t ) where - --t : (od→ord ( ord→od w)) o< (od→ord (ord→od x)) - --t = o<-subst lt ? ? - eq← lemma {w} lt = def-subst {suc n} {_} {_} {ord→od x} {w} {!!} refl refl - -od≡-def : {n : Level} → { x : Ordinal {suc n} } → ord→od x ≡ record { def = λ z → z o< x } -od≡-def {n} {x} = subst (λ k → ord→od x ≡ k ) oiso (cong ( λ k → ord→od k ) (≡-def {n} {x} )) - -==→o≡1 : {n : Level} → { x y : OD {suc n} } → x == y → od→ord x ≡ od→ord y -==→o≡1 eq = ==→o≡ (subst₂ (λ k j → k == j ) (sym oiso) (sym oiso) eq ) - -==-def-l : {n : Level } {x y : Ordinal {suc n} } { z : OD {suc n} }→ (ord→od x == ord→od y) → def z x → def z y -==-def-l {n} {x} {y} {z} eq z>x = subst ( λ k → def z k ) (==→o≡ eq) z>x - -==-def-r : {n : Level } {x y : OD {suc n} } { z : Ordinal {suc n} }→ (x == y) → def x z → def y z -==-def-r {n} {x} {y} {z} eq z>x = subst (λ k → def k z ) (subst₂ (λ j k → j ≡ k ) oiso oiso (cong (λ k → ord→od k) (==→o≡1 eq))) z>x +o<→o> : {n : Level} → { x y : Ordinal {suc n} } → (Ord x == Ord y) → x o< y → ⊥ +o<→o> {n} {x} {y} eq lt with ==→o≡ {n} eq +... | refl = o<¬≡ _ _ refl lt -∋→o< : {n : Level} → { a x : OD {suc n} } → a ∋ x → od→ord x o< od→ord a -∋→o< {n} {a} {x} lt = t where - t : (od→ord x) o< (od→ord a) - t = {!!} -o<∋→ : {n : Level} → { a x : OD {suc n} } → od→ord x o< od→ord a → a ∋ x -o<∋→ {n} {a} {x} lt = subst₂ (λ k j → def k j ) oiso refl t where - t : def (ord→od (od→ord a)) (od→ord x) - t = {!!} - -o∅≡od∅ : {n : Level} → ord→od (o∅ {suc n}) ≡ od∅' {suc n} -o∅≡od∅ {n} with trio< {n} (o∅ {suc n}) (od→ord (od∅' {suc n} )) -o∅≡od∅ {n} | tri< a ¬b ¬c = ⊥-elim (lemma a) where - lemma : o∅ {suc n } o< (od→ord (od∅' {suc n} )) → ⊥ - lemma lt with def-subst {suc n} {_} {_} {_} {_} ( o<→c< ( o<-subst lt (sym diso) refl ) ) refl diso - lemma lt | t = {!!} -o∅≡od∅ {n} | tri≈ ¬a b ¬c = trans (cong (λ k → ord→od k ) b ) oiso -o∅≡od∅ {n} | tri> ¬a ¬b c = ⊥-elim (¬x<0 c) - -o<→¬== : {n : Level} → { x y : OD {n} } → (od→ord x ) o< ( od→ord y) → ¬ (x == y ) -o<→¬== {n} {x} {y} lt eq = o<→o> eq lt - -o<→¬c> : {n : Level} → { x y : Ordinal {n} } → x o< y → ¬ (y c< x ) -o<→¬c> {n} {x} {y} olt clt = o<> olt {!!} where - -o≡→¬c< : {n : Level} → { x y : Ordinal {n} } → x ≡ y → ¬ x c< y -o≡→¬c< {n} {x} {y} oeq lt = o<¬≡ x y {!!} {!!} - -tri-c< : {n : Level} → Trichotomous _≡_ (_c<_ {suc n}) -tri-c< {n} x y with trio< {n} x y -tri-c< {n} x y | tri< a ¬b ¬c = tri< (def-subst {!!} oiso refl) {!!} ( o<→¬c> a ) -tri-c< {n} x y | tri≈ ¬a b ¬c = tri≈ (o≡→¬c< b) {!!} (o≡→¬c< (sym b)) -tri-c< {n} x y | tri> ¬a ¬b c = tri> ( o<→¬c> c) (λ eq → {!!} ) (def-subst {!!} oiso refl) - -c<> : {n : Level } { x y : Ordinal {suc n}} → x c< y → y c< x → ⊥ -c<> {n} {x} {y} x<y y<x with tri-c< x y -c<> {n} {x} {y} x<y y<x | tri< a ¬b ¬c = ¬c y<x -c<> {n} {x} {y} x<y y<x | tri≈ ¬a b ¬c = o<→o> {!!} {!!} -c<> {n} {x} {y} x<y y<x | tri> ¬a ¬b c = ¬a x<y +o<→¬== : {n : Level} → { x y : Ordinal {suc n} } → x o< y → ¬ (Ord x == Ord y ) +o<→¬== {n} {x} {y} lt eq = o<→o> {n} eq lt ∅< : {n : Level} → { x y : OD {n} } → def x (od→ord y ) → ¬ ( x == od∅ {n} ) -∅< {n} {x} {y} d eq with eq→ eq d +∅< {n} {x} {y} d eq with eq→ (eq-trans eq (eq-sym ∅0) ) d ∅< {n} {x} {y} d eq | lift () -∅6 : {n : Level} → { x : OD {suc n} } → ¬ ( x ∋ x ) -- no Russel paradox -∅6 {n} {x} x∋x = c<> {n} {{!!}} {{!!}} {!!} {!!} +-- ∅6 : {n : Level} → { x : OD {suc n} } → ¬ ( x ∋ x ) -- no Russel paradox +-- ∅6 {n} {x} x∋x = c<> {n} {{!!}} {{!!}} {!!} {!!} def-iso : {n : Level} {A B : OD {n}} {x y : Ordinal {n}} → x ≡ y → (def A y → def B y) → def A x → def B x def-iso refl t = t @@ -290,15 +227,14 @@ open _∧_ -¬∅=→∅∈ : {n : Level} → { x : OD {suc n} } → ¬ ( x == od∅ {suc n} ) → x ∋ od∅ {suc n} -¬∅=→∅∈ {n} {x} ne = def-subst (lemma (od→ord x) (subst (λ k → ¬ (k == od∅ {suc n} )) (sym oiso) ne )) oiso refl where - lemma : (ox : Ordinal {suc n}) → ¬ (ord→od ox == od∅ {suc n} ) → ord→od ox ∋ od∅ {suc n} - lemma ox ne with is-o∅ ox - lemma ox ne | yes refl with ne ( ord→== lemma1 ) where - lemma1 : od→ord (ord→od o∅) ≡ od→ord od∅ - lemma1 = cong ( λ k → od→ord k ) {!!} - lemma o∅ ne | yes refl | () - lemma ox ne | no ¬p = subst ( λ k → def (ord→od ox) (od→ord k) ) {!!} {!!} +ord-od∅ : {n : Level} → o∅ {n} ≡ od→ord (Ord (o∅ {n})) +ord-od∅ = ==→o≡ {!!} + + +¬∅=→∅∈ : {n : Level} → { x : Ordinal {suc n} } → ¬ ( Ord x == od∅ {suc n} ) → Ord x ∋ od∅ {suc n} +¬∅=→∅∈ {n} {x} ne with is-o∅ x +¬∅=→∅∈ {n} {x} ne | yes refl = ⊥-elim ( ne (eq-sym (eq-refl) )) +¬∅=→∅∈ {n} {x} ne | no ¬p = o<-subst (∅5 ¬p) ord-od∅ refl -- open import Relation.Binary.HeterogeneousEquality as HE using (_≅_ ) -- postulate f-extensionality : { n : Level} → Relation.Binary.PropositionalEquality.Extensionality (suc n) (suc (suc n)) @@ -321,6 +257,9 @@ L {n} record { lv = (Suc lx) ; ord = (Φ (Suc lx)) } = -- Union ( L α ) record { def = λ y → osuc y o< (od→ord (L {n} (record { lv = lx ; ord = Φ lx }) )) } +omega : {n : Level} → Ordinal {n} +omega = record { lv = Suc Zero ; ord = Φ 1 } + OD→ZF : {n : Level} → ZF {suc (suc n)} {suc n} OD→ZF {n} = record { ZFSet = OD {suc n} @@ -332,7 +271,7 @@ ; Power = Power ; Select = Select ; Replace = Replace - ; infinite = ord→od ( record { lv = Suc Zero ; ord = Φ 1 } ) + ; infinite = Ord omega ; isZF = isZF } where Replace : OD {suc n} → (OD {suc n} → OD {suc n} ) → OD {suc n} @@ -360,7 +299,7 @@ infixr 200 _∈_ -- infixr 230 _∩_ _∪_ infixr 220 _⊆_ - isZF : IsZF (OD {suc n}) _∋_ _==_ od∅ _,_ Union Power Select Replace (ord→od ( record { lv = Suc Zero ; ord = Φ 1} )) + isZF : IsZF (OD {suc n}) _∋_ _==_ od∅ _,_ Union Power Select Replace (Ord omega) isZF = record { isEquivalence = record { refl = eq-refl ; sym = eq-sym; trans = eq-trans } ; pair = pair @@ -383,7 +322,8 @@ proj1 (pair A B ) = omax-x {n} (od→ord A) (od→ord B) proj2 (pair A B ) = omax-y {n} (od→ord A) (od→ord B) empty : (x : OD {suc n} ) → ¬ (od∅ ∋ x) - empty x () + empty x (case1 ()) + empty x (case2 ()) --- --- ZFSubset A x = record { def = λ y → def A y ∧ def x y } subset of A --- Power X = ord→od ( sup-o ( λ x → od→ord ( ZFSubset A (ord→od x )) ) ) Power X is a sup of all subset of A @@ -412,7 +352,7 @@ eq← lemma-eq {z} w = record { proj2 = w ; proj1 = def-subst {suc n} {_} {_} {A} {z} ( t→A (def-subst {suc n} {_} {_} {t} {od→ord (ord→od z)} w refl (sym diso) )) refl diso } lemma1 : od→ord (ZFSubset A (ord→od (od→ord t))) ≡ od→ord t - lemma1 = subst (λ k → od→ord (ZFSubset A k) ≡ od→ord t ) (sym oiso) (==→o≡1 (lemma-eq)) + lemma1 = subst (λ k → od→ord (ZFSubset A k) ≡ od→ord t ) (sym oiso) {!!} lemma : od→ord (ZFSubset A (ord→od (od→ord t)) ) o< sup-o (λ x → od→ord (ZFSubset A (ord→od x))) lemma = sup-o< union-lemma-u : {X z : OD {suc n}} → (U>z : Union X ∋ z ) → csuc z ∋ z @@ -443,46 +383,25 @@ regularity : (x : OD) (not : ¬ (x == od∅)) → (x ∋ minimul x not) ∧ (Select (minimul x not) (λ x₁ → (minimul x not ∋ x₁) ∧ (x ∋ x₁)) == od∅) proj1 (regularity x not ) = x∋minimul x not - proj2 (regularity x not ) = record { eq→ = reg ; eq← = λ () } where + proj2 (regularity x not ) = record { eq→ = reg ; eq← = {!!} } where reg : {y : Ordinal} → def (Select (minimul x not) (λ x₂ → (minimul x not ∋ x₂) ∧ (x ∋ x₂))) y → def od∅ y reg {y} t with minimul-1 x not (ord→od y) (proj2 t ) - ... | t1 = lift t1 + ... | t1 = {!!} extensionality : {A B : OD {suc n}} → ((z : OD) → (A ∋ z) ⇔ (B ∋ z)) → A == B eq→ (extensionality {A} {B} eq ) {x} d = def-iso {suc n} {A} {B} (sym diso) (proj1 (eq (ord→od x))) d eq← (extensionality {A} {B} eq ) {x} d = def-iso {suc n} {B} {A} (sym diso) (proj2 (eq (ord→od x))) d - xx-union : {x : OD {suc n}} → (x , x) ≡ record { def = λ z → z o< osuc (od→ord x) } - xx-union {x} = cong ( λ k → record { def = λ z → z o< k } ) (omxx (od→ord x)) - xxx-union : {x : OD {suc n}} → (x , (x , x)) ≡ record { def = λ z → z o< osuc (osuc (od→ord x))} - xxx-union {x} = cong ( λ k → record { def = λ z → z o< k } ) lemma where - lemma1 : {x : OD {suc n}} → od→ord x o< od→ord (x , x) - lemma1 {x} = {!!} - lemma2 : {x : OD {suc n}} → od→ord (x , x) ≡ osuc (od→ord x) - lemma2 = trans ( cong ( λ k → od→ord k ) xx-union ) (sym ≡-def) - lemma : {x : OD {suc n}} → omax (od→ord x) (od→ord (x , x)) ≡ osuc (osuc (od→ord x)) - lemma {x} = trans ( sym ( omax< (od→ord x) (od→ord (x , x)) lemma1 ) ) ( cong ( λ k → osuc k ) lemma2 ) - uxxx-union : {x : OD {suc n}} → Union (x , (x , x)) ≡ record { def = λ z → osuc z o< osuc (osuc (od→ord x)) } - uxxx-union {x} = cong ( λ k → record { def = λ z → osuc z o< k } ) lemma where - lemma : od→ord (x , (x , x)) ≡ osuc (osuc (od→ord x)) - lemma = trans ( cong ( λ k → od→ord k ) xxx-union ) (sym ≡-def ) - uxxx-2 : {x : OD {suc n}} → record { def = λ z → osuc z o< osuc (osuc (od→ord x)) } == record { def = λ z → z o< osuc (od→ord x) } - eq→ ( uxxx-2 {x} ) {m} lt = proj1 (osuc2 m (od→ord x)) lt - eq← ( uxxx-2 {x} ) {m} lt = proj2 (osuc2 m (od→ord x)) lt - uxxx-ord : {x : OD {suc n}} → od→ord (Union (x , (x , x))) ≡ osuc (od→ord x) - uxxx-ord {x} = trans (cong (λ k → od→ord k ) uxxx-union) (==→o≡ (subst₂ (λ j k → j == k ) (sym oiso) (sym od≡-def ) uxxx-2 )) - omega = record { lv = Suc Zero ; ord = Φ 1 } infinite : OD {suc n} - infinite = ord→od ( omega ) - infinity∅ : ord→od ( omega ) ∋ od∅ {suc n} - infinity∅ = def-subst {suc n} {_} {o∅} {infinite} {od→ord od∅} - {!!} refl (subst ( λ k → ( k ≡ od→ord od∅ )) diso (cong (λ k → od→ord k) {!!} )) + infinite = Ord omega + infinity∅ : Ord omega ∋ od∅ {suc n} + infinity∅ = {!!} infinite∋x : (x : OD) → infinite ∋ x → od→ord x o< omega infinite∋x x lt = subst (λ k → od→ord x o< k ) diso t where t : od→ord x o< od→ord (ord→od (omega)) - t = ∋→o< {n} {infinite} {x} lt + t = {!!} infinite∋uxxx : (x : OD) → osuc (od→ord x) o< omega → infinite ∋ Union (x , (x , x )) - infinite∋uxxx x lt = o<∋→ t where + infinite∋uxxx x lt = {!!} where t : od→ord (Union (x , (x , x))) o< od→ord (ord→od (omega)) - t = subst (λ k → od→ord (Union (x , (x , x))) o< k ) (sym diso ) ( subst ( λ k → k o< omega ) ( sym (uxxx-ord {x} ) ) lt ) + t = subst (λ k → od→ord (Union (x , (x , x))) o< k ) (sym diso ) ( subst ( λ k → k o< omega ) {!!} lt ) infinity : (x : OD) → infinite ∋ x → infinite ∋ Union (x , (x , x )) infinity x lt = infinite∋uxxx x ( lemma (od→ord x) (infinite∋x x lt )) where lemma : (ox : Ordinal {suc n} ) → ox o< omega → osuc ox o< omega